980-nm, 15-W cw laser diodes on F-mount-type heat sinks. (December 2015) - Bezotosnyi, V.V.; Krokhin, O.N.; Oleshchenko, V.A.; Pevtsov, V.F.; Popov, Yu.M.; Cheshev, E.A.
Abstract: We have studied the key optical emission parameters of laser diodes (emission wavelength, ; stripe contact width, ) mounted directly on F- and C-mount-type copper heat sinks, without intermediate elements (submounts). When effectively cooled by a thermoelectric microcooler, the lasers on the F-mount operated stably at output powers up to . The lasers were tested for reliable operation at an output power of for, and no decrease in output power was detected to within measurement accuracy. The experimentally determined maximum total efficiency is 71.7 % and the efficiency at a nominal output power of is 61 %. We compare parameters of the laser diodes mounted on C- and F-mounts and discuss the advantages of the F-mounts.